THE EFFECT OF CONFIDENCE TOWARD SPEAKING PERFORMANCE OF SPEAKING STUDENTS OF SMART ILC PARE, KEDIRI - Fajria, Fildzah Syarafina Nur (Jurnal Pendidikan Bahasa Inggris Proficiency, 2019)
This research is aimed to know whether there is any positive and significant effect toward confidence and speaking performance of speaking students of Smart ILC or not. Descriptive quantitative method was used as the approach to design this research. The instrument used was questionnaires and test. The result was the positive and significant effect toward confidence and speaking performance of speaking students of Smart ILC is rejected. It means there is no significant effect toward confidence and speaking performance of speaking students of Smart ILC.